OHS ANALYSIS TO UNSAFE ACTION IN KERTOSONO – JOMBANG – MOJOKERTO – GEMPOL ROAD AND BRIDGE PRESERVATION PROJECT - Anara Bhisma Soca Driya; Fadjar Purnomo; Mochammad Khamim (Jurusan Teknik Sipil Politeknik Negeri Malang, 2024)
Road preservation project is one of the large-scale construction activities. PT Abipraya is one of the well-known contractors that carries out the project, therefore a proper OHS (Occupational Health and Safety) regulations are very important to establish. In this study an analysis of several OHS factors will be carried out which are considered to reduce the occurrence of unsafe acts. The factor used is the variable X1 namely